Emissions of CO2, N2O and CH4 From Cultivated and Set Aside Drained Peatland in Central Sweden - Berglund, Örjan; Kätterer, Thomas; Meurer, Katharina H. E. (Frontiers in Environmental Science, 2021)
Northern peatlands are important carbon (C) reservoirs, storing about one-third of the global terrestrial soil C pool. Anthropogenic influences, such as drainage for agriculture and forestry, lower the originally high groundwater level, leading to peat aeration and decomposition. This is particularly reflected in significant losses of CO2, while fluxes of N2O and CH4 are generally considered of minor importance for the overall greenhouse gas (GHG) balance of cultivated peatlands in Scandinavia. Setting land aside from agricultural production has been proposed as a strategy to reduce GHG emissions from drained peatland, restore natural habitats, and increase C sequestration. However, the evidence for this is rather scarce unless drainage is terminated. In this study, we measured respiration using dark automatic chambers, and CO2, N2O, and CH4 fluxes using manual static chambers, on: (i) cultivated peatland and (ii) adjacent set-aside peatland in Central Sweden. The set-aside site was found to be a greater source of CO2 emissions than the cultivated site, while higher N2O fluxes and lower CH4 uptake rates were observed for the cultivated site. However, to compare the full GHG balance and assess the abandonment of drained cultivated peatland, additional measurements, such as gross primary production (GPP) but also dissolved organic C losses would have to be taken into account.